Home-bAsed supportive, rehabilitative, and Palliative care theraPY (HAPPY) for COPD Patients in the community setting: A Rapid Review - Adnurrahman, Khadijah Fatiya; Agustina, Hana Rizmadewi; Firdaus, Rosalia; Mawaddah, Salwa (Alta Dharma Publisher, 2022)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is one of the non-communicable diseases caused by air pollution and is included in the world's top 10 causes of death. Objective: This literature review aims to identify interventions to improve the quality of life of COPD patients through the application of HAPPY (Home-bAsed Supportive, Rehabilitative, and Palliative Care TheraPY). The method used is a rapid review by searching for articles in four databases of Garuda, NCBI, NIH, and PubMed. The study reviewed was quantitative in English and Indonesian in adult patients with Obstructive Pulmonary Disease. Results: found several interventions, namely self-management, pursed-lip breathing exercise, self-care education, and family support. The management of complementary therapies based on home care has improved the health and quality of life of COPD patients. Conclusion: Based on the articles that have been obtained, both available treatments can be carried out for COPD patients, hospital-based management and home care therapy can be carried out to improve the quality of life of COPD patients with technological advances that are proven to facilitate complementary medicine, with an interdisciplinary approach to management COPD comprehensively.